A study to assess the socio-economic status of tea workers in selected tea estates of Sylhet district (Journal of the Bangladesh Agricultural University, 2017)
The study was carried out to examine the socio-economic characteristics of tea plantation workers. A total of 50 farmers from Sylhet district were selected randomly for data collection. The study showed that on an average the size of family of the tea workers was 4.69 which is lower than agricultural labourer inBangladesh. The dependency ratio was found to be 1.80.The literacy of the teaworkers was 56 percent out of which 43 percent were primary level and 13 percent were secondary level. The average annual income per surveyed household was Tk. 75,615 out of which 83% of the total income came from service as a tea labourer while rest 17% derived from agriculture and non-agricultural sources. On an average, the annual expenditure per family was Tk 64,053.The study observed that 88 % percent of the surveyed family received loan from different NGO,s and while only 12 percent obtained from the bank. The analysis credit utilization showed that 41% of the total loan was utilized in meeting repairing houses followed by purchasing of cows (25%) and business (13%) respectively. The study showed that hundred percent roofs of tea workers houses were made of tin. But 58% of the wall was made of brick while 42% was made of mud. On an average 47% of the families reared poultry while 63 percent had livestock. Fifty four percent of households grew vegetables in the study area. The major types of vegetables cultivate by tea workers in the study area were bean, lalsak, chalkumra, gourd etc. Majority household had fruit trees in their homestead. The study showed that most of the household consumed their home products. But only twenty one percent of the households sold their fruits in the local market for cash flow.